Hair diameter measurements for planning follicular unit extraction surgery (FUE): Is there a correlation between the micrometer caliper and scanning electron microscopy (SEM) findings?. (2nd June 2021) - Bayramoglu, Alp; Erdogan, Koray; Urhan, Oguzhan; Keskinoz, Elif Nedret; Acikel Elmas, Merve; Hayran, Mutlu; Arbak, Serap
Abstract: Background: Hair shaft diameter is one of the most important factors for the outcome of follicular unit extraction (FUE) surgery. In fact, the hair shaft is elliptical. Therefore, it has a long and short axis. Many hair transplantation surgeons use manual micrometer caliper for gauging hair diameter and use the results in the management of recipient and donor area. Aim: In this study, we aimed to identify the dependability of micrometer caliper and also the hair diameter diversity pattern in the donor area. Patients/Methods: Two hundred and seventy hairs were collected from three males with androgenetic alopecia. Hair samples were obtained from the 1 cm 2 boxes from superior to inferior at the mid‐point of temporal, parietal, and occipital donor areas. The diameter of each hair was measured both with a micrometer caliper and scanning electron microscopy (SEM). Results: Average diameter measured by scanning electron microscopy was 83.01 µm for the long axis and 51.51 µm for the short axis. The average value for the micrometer caliper measurement was 53.32 µm. Comparison of micrometer caliper results with the short‐axis measurements of SEM revealed a strong significant correlation. The hair diameters from superior, middle, and inferior boxes revealed a tendency to decrease toward the inferior regions. Conclusions: A manual micrometer caliper is a dependable tool for planning FUE surgery, and it measures the short axis of the elliptical hair shaft. Hair diameter tends to decrease toward the inferior regions of the donor area.